Effect of natural sweeteners on the physicochemical, nutritional, sensory, and microbiological properties of carrot-coconut gel pudding (International Journal of Agricultural Research, Innovation and Technology, 2026)
The market for sugar-reduced products is expanding rapidly due to increasing health awareness among consumers and advancements in sweetener technology. Consumers are actively seeking to reduce sugar intake, making sugar the primary ingredient targeted for reduction. Consequently, products labeled as "no added sugar," "sugar-free," or "low sugar" are gaining considerable popularity. Manufacturers are therefore developing innovative formulations to overcome challenges related to taste, texture, and consumer acceptability, ensuring the commercial viability of sugar-replaced gel puddings. This study was conducted to evaluate the effects of replacing refined sugar with natural sweeteners, dates, and honey, on carrot–coconut gel pudding. Seven formulations were prepared: a sugar-based control (S), honey-based samples (H1: 90g, H2: 80g, H3: 70g), and date-based samples (D1: 90g, D2: 80g, D3: 70g). Physicochemical properties, proximate composition, energy content, sensory attributes, and microbiological quality were analyzed. The results revealed that sample D1 (90g dates) exhibited the highest levels of crude fiber (12.88 ± 0.005%), vitamin A (30.85 ± 0.05 RAE/g), protein (4.12 ± 0.03%), fat (10.20 ± 0.00%), calcium (2.98 ± 0.02 mg/g), potassium (2.83 ± 0.02 mg/g), and sodium (68.90 ± 0.02 mg/g) among all formulations. In contrast, the sugar-based control demonstrated the highest energy value and overall sensory acceptability. No yeast or mold growth was detected in any sample during seven days of storage, while microbial load was comparatively higher in the control sample. Although sugar-based pudding exhibited higher energy content and acceptability, the date- and honey-based puddings-particularly the formulation containing 90g dates-offered significantly improved nutritional quality. These findings support the potential use of dates and honey as natural sweeteners for the development of healthier functional desserts.Int. J. Agril. Res. Innov. Tech. 15(2): 30-38, Dec 2025